2015
DOI: 10.1155/2015/734101
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antimicrobial Activity ofEuphrasia rostkovianaHayne Essential Oil

Abstract: Eyebright, Euphrasia rostkoviana Hayne (Scrophulariaceae), is a medicinal plant traditionally used in Europe for the treatment of various health disorders, especially as eyewash to treat eye ailments such as conjunctivitis and blepharitis that can be associated with bacterial infections. Some Euphrasia species have been previously reported to contain essential oil. However, the composition and bioactivity of E. rostkoviana oil are unknown. Therefore, in this study, we investigated the chemical composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The MIC values for these pathogens ranged from 0.097 to 6.25  μ L/mL. The antibacterial activity of Euphrasia rostkoviana essential oil against E. faecalis , E. coli , K. pneumoniae , S. aureus , S. epidermidis , and P. aeruginosa was reported by Novy et al [35]. In the study, all Gram-positive bacteria were effectively inhibited with an MIC of 512  μ g/mL.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 70%
“…The MIC values for these pathogens ranged from 0.097 to 6.25  μ L/mL. The antibacterial activity of Euphrasia rostkoviana essential oil against E. faecalis , E. coli , K. pneumoniae , S. aureus , S. epidermidis , and P. aeruginosa was reported by Novy et al [35]. In the study, all Gram-positive bacteria were effectively inhibited with an MIC of 512  μ g/mL.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 70%
“…The content of essential oil in the drug eyebright was 0.257%, whereas the level of the oil content in Euphrasia stricta reported by Miladinovic et al [2014] and E. rostkoviana analysed by Novy et al [2015] reached 0.02%. The GC-MS analysis revealed 28 constituents representing 99.96% of total oil content.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, our phytochemical analysis confirmed that substances such as pinene, linalool, terpineol, pulegone, caryphyllene, chamazulene, and cembrene, which represent various types of terpenes, were found in the essential oil in the eyebright. The data reported by other authors also showed that these substances are volatile constituents in Euphrasia stricta and E. rostkoviana [Miladinovic et al 2014, Novy et al 2015. The terpene compounds are responsible for the antioxidant, antiviral, antibacterial, and antifungal properties [Thoppil and Bishayee 2011].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations